Working Identities: Review of Lindsay Hamilton and Nik Taylor, Animals at Work. Identity, Politics, and Culture in Work with Animals - Baár, Monika (Humanimalia, 2016)
Lindsay Hamilton and Nik Taylor, Animals at Work. Identity, Politics, and Culture in Work with Animals. Leiden: Brill, 2013, xiv, 196 pp. €104.00; $133.00 (pb).